Survive [videorecording (DVD)] - Abate, Richard; Ungar, Jeremy; Turner, Sophie, 1996-; Hawkins, Corey, 1988-; Foxx, Dane (Freestyle Digital Media, 2023)
Two ordinary people, Jane and Paul, are the only survivors of a plane crash that isolates them on a remote snow-covered mountain. Soon this unlikely duo will have to find a way to get back to society, all while Jane struggles with her demons and Paul does everything he can to keep her safe.